Soil microbial diversity and composition: Links to soil texture and associated properties. (October 2020) - Xia, Qing; Rufty, Thomas; Shi, Wei
Abstract: Soil texture is an essential component of soil survey for estimating potentials and limitations of land use and management. It has been appreciated as an important predictor for numerous soil processes. However, its connections with the diversity and composition of the soil microbial community remain less understood. This work employed a marker gene high-throughput sequencing approach to determine soil texture-based patterns of bacterial and fungal distribution. Thirty-six intact soil cores were sampled from bermudagrass ecosystems across seven soil texture classes with sand fraction varying from 30.3 to 83.4% and clay fraction from 4.4 to 53.0%. These soil cores were arranged into three sets of equal numbers, and each set of 12 was subjected to three moisture regimes (dry spell, field moisture, and saturation-field capacity), respectively, for 15 days. Soil cores were further stratified into top and bottom sections, leading to a total of 72 samples with varying soil physical and chemical properties. Our data revealed that fungal alpha diversity was more strongly related to soil texture than bacterial alpha diversity, with fungal species richness and Shannon diversity being positively correlated with the sand fraction. Soil texture was the second most important factor after soil pH in shaping the soil microbial community. Relative abundances of some fungi (Basidiomycota and Eurotiomycetes) and filamentous bacteria (Actinobacteria, Chloroflexi) significantly increased with silt and/or clay content. The genetic potential for the degradation of organic compounds also appeared to be higher in finer textured soils than the coarse-textured soils. By identifying sand, silt or clay-preferred microbial taxa and characterizing mineral particle-dependent genetic potential of organic carbon degradation and nitrogen cycling, this work highlighted the significance of soil texture and texture-associated pores, and resource locality, in regulating microbial diversity and community composition. Highlights: Soil texture ranked second after pH in shaping the soil microbial community. Texture effects on alpha diversity were stronger for fungi than bacteria. Coarse textured soils promoted fungal species richness. Silt and clay fractions helped to increase filamentous bacteria and some fungi. Finer textured soils had a greater genetic potential to degrade organic carbon.